Frequency of health service use in the year prior to asthma death. (27th May 2016) - To, Teresa; Zhu, Jingqin; Williams, Devon P; Feldman, Laura; Simatovic, Jacqueline; Gershon, Andrea; Lougheed, M. Diane; Licskai, Christopher; Dell, Sharon
Abstract: Objective : High frequency health service use (HSU) is associated with poorly controlled asthma, and is a recognized risk factor for near-fatal or fatal asthma. The objective of this study was to describe the frequency of HSU in the year prior to asthma death. Methods : Individuals aged 0–99 years who died from asthma from April 1996 to December 2011 in Ontario, Canada were identified as cases. Cases were matched to 4–5 live asthma controls by age, sex, rural/urban residence, socioeconomic status, duration of asthma and a co-diagnosis of COPD. HSU records in the year prior to death [hospitalization, emergency department (ED) and outpatient visits] were assembled. The association of prior HSU and asthma death was measured by conditional logistic regression models. Results : From 1996 to 2011, 1503 individuals died from asthma. While the majority of cases did not have increased HSU as defined in the study, compared to matched live asthma controls, the cases were 8-fold more likely to have been hospitalized two or more times (OR = 7.60; 95% CI: 4.90, 11.77), 13-fold more likely to have had three or more ED visits (OR = 13.28; 95% CI: 7.55, 23.34) and 4-fold more likely to have had five or more physician visits for asthma (OR = 4.41; 95% CI: 3.58, 5.42). Conclusions : Frequency of HSU in the year prior was substantially higher in those died from asthma. Specifically, more than one asthma hospital admission, three ED visits or five physician visits increased the asthma mortality risk substantially and exponentially.